2019
DOI: 10.3390/nu11123049
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Vitamin D Insufficiency among Adolescent Girls and Young Adult Women from Korea

Abstract: Although there is evidence of the biological mechanisms by which obesity may induce vitamin D insufficiency or deficiency, limited epidemiological studies have been conducted, especially among Asian adolescent girls and young adult women who are at a high risk of vitamin D deficiency. This study aimed to examine the cross-sectional association between obesity and vitamin D insufficiency among adolescent girls and young adult women in Korea. We used data from the Korea National Health and Nutrition Examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Lactobacillus plantarum supplementation has been shown to reduce anxiety- and depression-like behaviours in rodents 27 29 . Supplementation with Lactobacillus reuteri reduced stress-induced anxiety-like behaviours 30 and restored disturbed social behaviour in mice with an unbalanced gut microbiota 31 . Meta-analyses also suggest that probiotic supplementation in humans can reduce subjective stress levels without altering cortisol levels 32 and has antidepressant and anxiolytic effects 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus plantarum supplementation has been shown to reduce anxiety- and depression-like behaviours in rodents 27 29 . Supplementation with Lactobacillus reuteri reduced stress-induced anxiety-like behaviours 30 and restored disturbed social behaviour in mice with an unbalanced gut microbiota 31 . Meta-analyses also suggest that probiotic supplementation in humans can reduce subjective stress levels without altering cortisol levels 32 and has antidepressant and anxiolytic effects 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The Korea National Health and Nutrition Examination Survey indicated that vitamin D insufficiency is among the risk factors of dental caries in permanent dentition in children and adolescent girls (Jang, Lee, & Park, 2019; Kim, Lee, Ju, Na, & Oh, 2018). Vitamin D is available in two forms: cholecalciferol and ergocalciferol.…”
Section: Introductionmentioning
confidence: 99%
“…Weight and height were measured with the participants wearing no shoes and were used to define BMI. The World Health Organization criteria were used in the present study for the Chinese population and 3 BMI (kg/m 2 ) categories were provided as follows: normal weight (18.5-22.9 kg/m 2 ), overweight (22.9-24.9 kg/m 2 ), and obese (>25.0 kg/m 2 ) ( 20 ). The grip strength of both hands was determined with a hand dynamometer and five-times-sit-to-stand test (FTSST) was used to evaluate the physical function.…”
Section: Methods and Analysismentioning
confidence: 99%